Exploring studies on multimodal literacy in English learning: a bibliometric analysis - Christian, Ivan Samuel; Rohmah, Zuliati; Jalaluddin, Ilyana (Sekolah Tinggi Agama Islam Negeri (S T A I N) Kediri, 2024)
This study focuses on analyzing the productivity of research in multimodal literacy in English learning by using bibliometric analysis. A total of 345 articles from the Scopus database were retrieved using keyword searches. The bibliometric data were analyzed using Biblioshiny in R and VOSviewer to analyze the most prolific authors, the total number of publications and citations, the publication productivity of each country and the total number of citations per country, the number of publications from affiliations, the number of publications from sources, and the keywords that often appear as material for trend analysis. The results of this study show that Jiang L is the researcher with the biggest number of publications in this field among the most prolific authors. The countries with the most publications and citations are the USA and China. Nanyang Technological University, Michigan State University, and Griffith University are the three highest affiliations that produce publications in this field. In the keyword analysis, it was found that multimodality, literacy, multiliteracies, and digital/media literacies are popular keywords that determine trends and are connected to new keywords such as writing, instructional strategies, digital multimodal composing, ELL, critical thinking, challenges, curriculum design, drawing, apps, popular cultures and instructional strategies that are emerging in this field.